In vitro anticariogenic activity of aqueous extract of Psidium guajava leaf against Streptococcus oralis - A dormant pathogen for dental caries - K U Keerthi; M D Dinesh; S Suji; K P Anagha; K V Anju; R Vismaya (Wolters Kluwer Medknow Publications, 2023)
Background: Dental caries is a complicated, multifaceted illness that affects teeth and leads to serious cavities both inside and outside the teeth. Aim: This study aims to determine the efficacy of Psidium guajava leaf extract against Streptococcus oralis. Materials and Methods: P. guajava leaves were extracted in water using the Soxhlet technique, and to identify the existence of several beneficial substances, phytochemical screening was carried out. The inhibitory properties of the aqueous extract were tested against S. oralis. Antimicrobial activity was determined by the agar well diffusion method. The minimum inhibitory concentration (MIC) was determined by the liquid dilution method, and the minimum bactericidal concentration (MBC) was determined by the agar plate method. Results: Qualitative analysis of phytochemicals by standard methods showed the presence of various bioactive compounds. Using the well diffusion method, it has been determined that P. guajava leaf extract has antibacterial activity against S. oralis. The determination of the MIC and MBC showed that the extract exhibited an antimicrobial effect against cariogenic bacteria. Conclusion: P. guajava leaf extract contains bioactive compounds that have a significant impact on the avoidance of dental cariogens. P. guajava leaf extract is effective against S. oralis.